2020
DOI: 10.1371/journal.pone.0243058
|View full text |Cite
|
Sign up to set email alerts
|

Is microaggression an oxymoron? A mixed methods study on attitudes toward racial microaggressions among United States university students

Abstract: To best understand the possible negative health and social consequences associated with racial microaggression, in-depth understanding of how people judge these events is needed. People of Color (POC) and White participants (N = 64) were recruited for a mixed-methods study that incorporated quantitative attitude ratings and focus group interviews. Participants read and discussed their attitudes toward five vignettes that reflected microassault, microinsult, and microinvalidation scenarios. Semantic differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
(101 reference statements)
3
22
0
Order By: Relevance
“…The SD method operationalizes qualitative information, measuring respondents' affective, and attitudinal states based on the attributional meaning given to items (Osgood et al, 1957). The methodology is well established as a reliable and effective way to measure attitudes, preferences, and perceptions resulting from real-life experience (e.g., Hiessl and Skrandies, 2013;Lui et al, 2020;Paterlini et al, 2021;Sobolev et al, 2021). The research conducted by Osgood et al (1957), on different objects of investigation and among culturally different samples, showed that the SD method can highlight "latent cognitive structures" commonly referring to three different dimensions, mutually independent.…”
Section: Methodsmentioning
confidence: 99%
“…The SD method operationalizes qualitative information, measuring respondents' affective, and attitudinal states based on the attributional meaning given to items (Osgood et al, 1957). The methodology is well established as a reliable and effective way to measure attitudes, preferences, and perceptions resulting from real-life experience (e.g., Hiessl and Skrandies, 2013;Lui et al, 2020;Paterlini et al, 2021;Sobolev et al, 2021). The research conducted by Osgood et al (1957), on different objects of investigation and among culturally different samples, showed that the SD method can highlight "latent cognitive structures" commonly referring to three different dimensions, mutually independent.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that its use to refer to experiences of different demographic groups from those about whom it was first explored has weakened its power and that “racial abuse” should be used instead, particularly for the experiences of Black people (Kendi, 2019). The affix of “aggression” within the term microaggression has been described as overly pejorative (Lilienfeld, 2017) and oxymoronic when combined with the root, “micro,” which suggests something trivial (Priscilla Lui et al, 2020). Ultimately, any term should achieve two things: give weight to people’s lived experiences and generate understanding in those who do not have that experience.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from qualitative and naturalistic survey research can inform the empirical questions that are addressed in VR studies and guide the design of VR simulations. In some of our own research, focus group participants deemed a set of written vignettes to be representative of real-life discrimination-related experiences, and we turned these scenarios into scripts and interactions within an immersive virtual environment (Lui, Berkley, et al, 2020; Lui, Pham, et al, 2020).…”
Section: Using Virtual Reality In Experimental Researchmentioning
confidence: 99%